EXPERIMENTAL TREATMENT INVOLVING APITHERAPY IN HEREDITARY HEMOLYTIC ANEMIA - Calin Vasile ANDRITOIU; Vasile ANDRITOIU; Gabriela Ildiko ZONDA; Liliana FOIA; Mihai CARLAN; Marcel COSTULEANU (Romanian Dental Association for Education, 2013)
Hemolytic anemia is a form of anemia in which red blood cells are destroyed and removed from the bloodstream before their usual lifespan is up. Anemia appears because the red blood cells are destroyed faster than the bone marrow can produce them. The etiology of premature erythrocyte destruction is diverse and can be due to conditions such as intrinsic membrane defects (hereditary spherocytosis, hereditary elliptocytosis), abnormal hemoglobins (sickle cell disease, thalassemia), erythrocyte enzymatic defects (G-6-PD deficiency, pyruvate kinase deficiency), immune destruction of erythrocytes, mechanical injury, and hypersplenism. Intrinsic hemolytic anemias are often inherited; these conditions produce red blood cells that do not live as long as normal red blood cells. Classical treatment of hereditary hemolytic anemia consists of corticosteroids, splenectomy, immunosuppressive drugs or plasmapheresis. The purpose of our study was to assess the effects of an experimental apitherapy treatment on a batch of mutant mice with hereditary hemolytic anemia.